Endurance training and testing with the ball in young elite soccer players. Issue 1 (23rd December 2004) - Chamari, K; Hachana, Y; Kaouech, F; Jeddi, R; Moussa-Chamari, I; Wisløff, U
Abstract : Background: The aerobic capacity of soccer players substantially influences their technical performance and tactical choices. Thus, the assessment of soccer players' aerobic performance should be of interest for soccer coaches in order to evaluate and improve their endurance training sessions. In this study, we present a new test to assess aerobic performance in soccer by means of a specific dribbling track: the Hoff test. We further determined whether improvement in maximal oxygen uptake was reflected in increased distance covered in the Hoff test. Methods: We tested 18 male soccer players (14 years old) both in the laboratory and using the Hoff test before and after 8 weeks of soccer training. Results: The distance covered in the Hoff test correlated significantly with maximum oxygen uptake, and improved by 9.6% during the 8 week training period, while maximum oxygen uptake and running economy improved by 12 and 10%, respectively. Backward multiple regression showed maximum oxygen uptake to be the main explanatory variable for the distance covered in the Hoff test. Conclusion: The present study demonstrated a significant correlation between laboratory testing of VO2max and performance in the Hoff test. Furthermore, training induced improvements in VO2max were reflected in improved performance in the Hoff test. We suggest that it should be a goal for active U-15 soccer players to cover more than 2100 metres in the Hoff test, as this requires a VO2max of above 200 ml/kg 0.75 /min, which should serve as a minimum in modern soccer.